Hillside Agriculture Sub-project (HASP) Costs and returns Under different tecnology packages for fruit trees - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
76 Páginas. Series Miscellaneous publication series A2/JM-94/010.